Rationally Designed Porous Silicon As Platform For Optical Biosensors - Priano, G (2012)
Optical porous silicon multilayer structures are able to work as sensitive chemical sensors or biosensors based in their optical response. An algorithm to simulate the optical response of these multilayers was developed, considering the optical properties of the individual layers. The algorithm allows designing and customizing the porous silicon structures according to a given application. The results obtained by the simulation were experimentally verified; for this purpose different photonic structures were prepared, such as Bragg reflectors and microcavities. Some of these structures have been derivatized by the introduction of aminosilane groups on the porous silicon surface. The algorithm also permits to simulate the effects produced by a non uniform derivatization of the multilayer.